The challenge of enhancing a luxury brand without awareness in a perfumery - Gregório, Vânia Catarina Pereira de Barros (2015)
The secret of beauty and attractiveness has been a quest of humans for as long as we have been civilized. People, naturally, seek to attract attention and society is increasingly accustomed living around of beauty. Everywhere, every time people are expected to be beautiful and know exactly what appeals to their sense of beauty. And it is not just a question of hairstyle or clothes they wear anymore; it is also a question of how well and confident they are. Whether it’s a night out or just another day at work, perfume makes people feel completed because it fits with their personality and influences their moods. As the world-renowned wizards of conceptual fashion, Viktor & Rolf (V&R) are known for inventing surreal twists on conventional design. Combining luxury and fashion into a perfume, V&R provide more than fragrances; it defines the character of the purchaser. Huge advantage, once most fashion brands would die to be characterized as luxury but only a few, in fact, are. However, without awareness there is no dream and that could be a challenge for many luxury brands. V&R will be used as reference to create a case that challenges students to better understand how to promote a luxury brand and how to upgrade the service on perfumeries. In order to support the target of this case study with a valuable and practical tool about the topic of Luxury Brands Marketing strategy, it was developed an extensive research on how to deal and communicate Luxury Brands.